General and specific combining abilities of popcorn for the High Valleys of Mexico - Martínez-Díaz, Francisco Sebastián; García-Zavala, J. Jesús; Espinosa-Calderón, Alejandro; Tadeo-Robledo, Margarita; Lobato-Ortiz, Ricardo; Ambrosio Gil , Eduardo (Revista Mexicana de Ciencias Agrícolas, 2025)
The demand for popcorn (Zea mays L.) in Mexico is increasing every day, but its annual national production is insufficient, and the demand of 80 thousand tonnes is fulfilled with imports. The supply of improved national varieties of this type of corn is very scarce. In order to identify outstanding popcorn materials, this work estimated the effects of general and specific combining abilities, and maternal and reciprocal effects for the yield of six elite populations of popcorn and their diallel crosses. The materials were evaluated in an experimental design of randomized complete blocks with three replications in 2018, 2019 and 2020. According to the results, population 6 (PB6), due to its high yield, would have a high contribution to the expression of the yield of its progeny and could be included in a genetic breeding program for popcorn. The crosses with the highest specific combining ability for yield were PB3 x PB6 and PB6 x PB3, respectively. The popcorn populations in this work that presented high effects of general combining ability for yield can be used to develop synthetic varieties or continue to advance them with more selection cycles, while crosses with high specific combining ability can be used to obtain popcorn hybrids in Mexico.
Keywords: Zea mays L.; general combining ability; popcorn; specific combining ability; populations; yield